This Universe Is the `Best' of All Possible Worlds. A Tentative Reconstruction of the Metaphysical System of Leo Apostel - Christiaens, Wim (Philosophica, 2001)
After presenting Apostels views on scientific realism, I present definitions of the concepts of ontology and metaphysics. I then proceed to develop Apostels basic ontology and his metaphysics. Apostel proposed a particular understanding of existence based on his views on causation. He also developed a view of the universe as a causal self-explaining system. I discuss and illustrate three kinds of what he calls metaphysical deductions that aim to deliver such a view of the universe. The most important one is the Leibnizian variational method, that should allow us to deduce the existing universe as the best of all possible worlds.